Perencanaan Program Corporate Social Responsibility Berkelanjutan di Wisata Dusun Semilir - Rossa Rahmawati, Erika; Kristiyani , Dian Novita (JIKE: Jurnal Ilmu Komunikasi Efek, 2024)
Corporate Social Responsibility is a form of corporate concern towards stakeholders as a corporate responsibility effort to help prepare internal and external needs and interests. The problem faced by Dusun Semilir is the lack of time to plan and implement programmes properly, the failure to consider in depth various aspects, such as the needs of local communities, the resources available, or the potential impact of such programmes. Dusun Semilir tourism is still doing CSR activities that are incidental. The concept of implementing corporate social responsibility that has been implemented is still limited to activities such as the distribution of prizes or gifts in anticipation of the great day of religion, charity, and the provision of assistance after natural disasters and other events. The aim of this research is to know how the CSR program and its impact as well as to know the planning of CSR programs Dusun Semilir Tourism sustainably. Researchers use qualitative research methodologies. Data collection techniques used, namely, interviews, observations, and using data collection analysis techniques, data reduction, and data presentation. The results of this research are in the planning of this CSR program Tourism Dusun Semilir has a major step in the implementation of CSR consisting of 3 stages, pre-implementation, implementation as well as monev (monitoring dan evaluasi). Taking such measures can result in benefits such as improved corporate reputation, customer loyalty, consumer satisfaction, and corporate sustainability. It helps companies mitigate risks and take advantage of opportunities related to social and environmental issues.